Non-targeted metabolomics and pseudo-targeted lipidomics combined with gut microbes reveal the protective effects of Causonis japonica (Thunb.) Raf. in ulcerative colitis mice - Huang, Hua; Jiang, Jie; Fan, Yihua; Ding, Xufeng; Li, Fang (Frontiers in Cellular and Infection Microbiology, 2024)
Ulcerative colitis (UC) is an inflammatory bowel disease characterized by recurrent inflammatory tissue damage to the intestinal mucosa and forming intestinal epithelial ulcers. It is one of the most intractable diseases in the world. To date, the mechanism is unclear. Causonis japonica (Thunb.) Raf. (Wu Lianmei in Chinese; WLM), a traditional Chinese medicine, which has a long history as an anti-inflammatory, but its effect on UC was unconfirmed yet. Therefore, we established a dextran sodium sulfate (DSS)-induced UC mice model and evaluated the therapeutic effect of WLM extract. The results indicated that WLM inhibits DSS-induced inflammatory response in colitis in vivo, decrease DSS-induced clinical manifestations, reverses colon length shortening, and reduces tissue damage. The results of ELISA kits suggested that WLM could reverse the levels of DSS-induced inflammatory factors. To explore the mechanism of WLM in treating DSS-induced UC, 1H NMR and UHPLC-Q/Orbitrap MS were used to perform non-targeted metabolomics analysis; 21 differential metabolites in colon tissues were closely related to UC. Meanwhile, the pseudo-targeted lipidomics based on UHPLC-Q/Trap MS was used to analyze lipid metabolism disorders, and 60 differential lipid compounds were screened. These differential compounds were mainly involved in glycerophospholipid, arachidonic acid, glycerolipid, citric acid, tyrosine, and ether lipid metabolisms. The analysis of gut microbial showed that WLM may improve the symptoms of UC mice by reducing the abundance of Helicobacter and Streptococcus and increasing the abundance of Limosilactobacillus and Akkermansia. Moreover, the real-time qPCR results showed that WLM extract could decrease the mRNA levels of inflammatory factors and may be associated with protecting the integrity of intestinal mucosal barrier by destroying in vivo metabolic pathways, especially by regulating energy and lipid metabolisms and reducing inflammatory reactions. It provides a beneficial reference for studying WLM to elucidate the therapeutic mechanism of UC.